Masterpiece iconic houses by great contemporary architects - Browne, Beth (Mulgrave, Victoria Images Publishing, 2012)
Every great architect has an original vision. The ability of master architects to see the big picture, to create inclusive, responsive designs that embrace building, site, and interiors with subtlety and style, leads to their work gaining widespread praise and international acclaim. Their talent and ambition, along with an unfaltering attention to detail and flair for fusing art and architecture, combine to produce houses of unparalleled style and comfort. Masterpiece: Iconic Houses by Great Contemporary Architects presents an up-to-the-minute collection of residential work from these much-lauded practitioners, proving that architecture can always be re-imagined. This invaluable new compendium of spectacular houses designed by architecture?s brightest stars also provides unique insights into their personal design philosophies. Stunning architectural photography of each house is supplemented with detailed descriptions, plans, sections, and sketches, revealing the mastery behind each design. Project locations range from the USA to France, from Italy to Dubai, and from Hong Kong to Spain.
5°35? at Craignish / Cameron Webster Architects -- Berberian Residence / Landry Design Group -- Bridge House / Stanley Saitowitz/Natoma Architects, Inc. -- Brussels House / Philippe Samyn and Partners -- Carillo Residence / Ehrlich Architects -- Drumlin Hall / Peter Pennoyer Architects -- Ganendra Art House/ Ken Yeang -- The Hen House / Rural design -- Hill House / MacKay-Lyons Sweetapple Architects -- Hong Kong Villa / Olson Kundig Architects -- The Houl / Simon Winstanley Architects -- House of Passages / Ken Tate Architect -- The House of Planes/The House of Volumes / Margaret McCurry with Stanley Tigerman -- Huckleberry House / Allan Greenberg Architect -- Jaspers Loft / Michel Jaspers -- Kawana House / Foster + Partners -- Kokkalis House / BC Estudio -- Lake Residence / Charles R. Stinson Architects -- Lakeshore View / SCDA Architects -- Lawson-Westen House / Eric Owen Moss Architects -- Linear House / Patkau Architects -- Lyle House / William T. Baker -- Massachusetts residence / CBT Architects -- Miracle Beach House / Helliwell + Smith, Blue Sky Architecture -- Modern classical house / Robert Adam, Adam Architecture -- Montecito Residence / Barton Myers Associates -- Mortlock Lee House / Troppo Architects NT -- Mount Davis Villa / Farrells -- Oz House / Swatt/ Miers Architects -- Padaro Beach House / B3 Architects -- Palo Alto Residence / CCS Architecture -- Pool House Dubai / chakib Richani Architects -- Riverbank House / Jackson Architecture -- Ruddell House / Moore Ruble Yudell Architects and Planners -- Schnabel House / Gehry Partners -- Sierra Residence / Arkin Tilt Architects -- Simpson-Lee House / Glenn Murcutt -- skyarc / will bruder+Partners -- Sycamores Estate / Richard Manion Architecture -- Turbulence House / Steven Holl Architects -- Villa in Lyngby / Henning Larsen Architects -- Villa Redaelli / Mario Botta -- Villa S / Coop Himmelb(L)au -- Villa Veneto / Michael Suttor -- Virginia Ranch / Diamond Schmitt Architects.
Keywords: Architect-designed houses -- History -- 20th century -- Pictorial works; Architect-designed houses -- History -- 21st century -- Pictorial works; Architect-designed houses -- Designs and plans